Case Report: Primary Leptomeningeal Medulloblastoma in a Child: Clinical Case Report and Literature Review - Morgacheva, Daria; Daks, Alexandra; Smirnova, Anna; Kim, Aleksandr; Ryzhkova, Daria; Mitrofanova, Lubov; Staliarova, Alena; Omelina, Evgeniya; Pindyurin, Alexey; Fedorova, Olga; Shuvalov, Oleg; Petukhov, Alexey; et al. (Frontiers in Pediatrics, 2022)
Medulloblastoma is one of the most common pediatric CNS malignancies worldwide and it is characterized by frequent leptomeningeal metastasizing. We report a rare case of primary leptomeningeal medulloblastoma of 11-year-old Caucasian girl with a long-term disease history, nonspecific clinical course and challenges in the diagnosis verification. To date, 4 cases of pediatric primary leptomeningeal medulloblastoma are reported, and all of them are associated with unfavorable outcome. The approaches of neuroimaging and diagnosis verification are analyzed in the article to provide the opportunities for effective diagnosis of this disease in clinical practice. The reported clinical case of the primary leptomeningeal medulloblastoma is characterized by MRI picture with nonspecific changes in the brain and spinal cord, and 18FDG-PET/CT images with diffuse heterogeneous hyperfixation of the radiopharmaceutical along the whole spinal cord. The IHC and NGS analyses of tumor samples were performed for comprehensive characterization of the reported clinical case.